Accelerating out of the great recession [ how to win in a slow-growth economy - Rhodes, David; Stelter, Daniel , 1964- (McGraw-Hill, 2010)
Delivers useful information, including comprehensive, big-picture analysis of the global economic downturn, and practical guidance for how to take advantage during recovery phases. This title uses case studies of businesses that have mastered past economic downturns and emerged as leaders in their respective markets and sectors.